2023
DOI: 10.1155/2023/7950026
|View full text |Cite
|
Sign up to set email alerts
|

Role of Royal Jelly Treated Adipose‐Derived Stem Cell‐Extracellular Vesicles on Fibroblast Proliferation, Migration, and Collagen Production

Abstract: Extracellular vesicles (EVs) secreted from adipose-derived stem cells (ADSCs) are known to exhibit collagen synthesis and migration activity in fibroblasts. These EVs can be used as a regenerative medicine and for cosmetic medicinal materials. Royal jelly (RJ) is produced from the hypopharyngeal and mandibular glands of honeybees (nurse bee), which contains apicin and 10-hydroxy-2-decenoic acid, compounds that promote fibroblast proliferation and collagen and elastin synthesis. Here, we investigated whether RJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Recently, an experiment using umbilical cord-derived MSCs revealed that RJ treatment contributes to the reduction of senescent cells and the maintenance of mitochondrial function [15]. It was also reported that RJ stimulated the secretion of extracellular vesicles in adipose-derived MSCs, leading to collagen synthesis in the dermal fibroblast [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an experiment using umbilical cord-derived MSCs revealed that RJ treatment contributes to the reduction of senescent cells and the maintenance of mitochondrial function [15]. It was also reported that RJ stimulated the secretion of extracellular vesicles in adipose-derived MSCs, leading to collagen synthesis in the dermal fibroblast [16].…”
Section: Introductionmentioning
confidence: 99%